Analisis Campuran Limbah Kotoran Sapi dan Tahu dalam Menghasilkan Biogas di Desa Sukamulia - Apsari, Ayas Ditha; Munandar, Rizky; Wahyuni, Atika; Makhrus, Muh; Kamilatunnisa, Laili; Solihin, Isnam (Journal of Science Technology and Education, 2025)
Analysis of a mixture of cow dung and tofu waste in producing biogas in Sukamulia Village. Biogas is a natural gas produced by the breakdown of organic matter through an anaerobic process and can produce energy. This study aims to analyze a mixture of cow dung and tofu waste in producing biogas in Sukamulia Village. The study used an experimental method by measuring the DO, BOD, COD, TSS and TDS content in the waste, as well as measuring the mass of biogas. The study was conducted for 4 months in Sukamulia Village. The results obtained showed DO measurement results of 1.2 mg/L, BOD of 10.9 mg/L, COD of 13.6 mg/L, TSS of 2,557 mg/L and TDS of 2,220 mg/L. Based on the measurement of biogas mass, an average value of 1.5 grams/day was obtained. The biogas produced was able to burn for 3.2 minutes with a small flame size. Analysis of a mixture of cow dung and tofu waste can produce biogas and be a solution to overcome pollution by cow dung and tofu waste.